Faktor Penyebab dan Upaya Penanggulangan Kejahatan Pencurian yang Dilakukan Anak di Kota Kupang - Sherly Floresti Anin; Rudepel Petrus Leo; Adrianus Djara Dima (Universitas Sains dan Teknologi Komputer, 2024)
Children are part of the generation that will continue the ideals and also serve as the foundation and hope of the nation. A child's background must be to do positive things to prepare them for life in the future, for example going to school and interacting with a positive environment. However, in reality, quite a lot of children are involved in negative things, for example theft. The formulation of the problem in this research is: (1) What are the factors that cause criminal acts of theft committed by children in Kupang City? (2) What countermeasures have been taken to overcome the occurrence of criminal acts of theft committed by children in Kupang City? This research is empirical juridical research and the data used are primary, secondary and tertiary data. This research used interviews with 19 respondents. The data was processed and analyzed descriptively qualitatively. The results of this research show that: (1) The factors causing theft committed by children come from internal factors or from within the perpetrator and external factors or from the environment where the perpetrator lives. (2) Efforts to overcome perpetrators by children: (a) Preemptive efforts, namely efforts made to instill good values ​​or norms. (b) Preventive efforts, namely preventing crimes before they occur. To optimize handling of this problem, the author suggests paying attention to several things: (1) The public is expected to further improve security in their residential environment to prevent theft crimes. (2) The police are expected to be more intensive in their efforts to prevent criminal acts from occurring in order to reduce criminal acts of theft that occur in Kupang City.